Clinical, Epidemiological, and Laboratory Profiles of Mediterranean Spotted Fever among Pediatric and Adult Patients in Eastern Libya: A Retrospective Cohort Study - Arij Abdelgader (Attahadi Medical Journal, 2026)
Mediterranean spotted fever (MSF) is a tick-borne rickettsiosis and continues to be endemic in the Mediterranean basin, but relatively little contemporary clinical data exist from Libya. This study characterized the epidemiological, clinical, laboratory, and seasonal profile of clinically diagnosed MSF and identified factors associated with severe disease. A hospital-based retrospective observational study was conducted among consecutive paediatric and adult patients managed at Al-Bayda Medical Center, Libya, from January to December 2024. Data on demographics, epidemiology, clinical characteristics, laboratory findings, treatment, and follow-up outcomes were collected from medical records. Severe disease was defined as admission to the intensive care unit (ICU) or in-hospital mortality. IBM SPSS Statistics version 29.0 was used to analyse the data. A total of 117 patients were included, of whom 87 (74.4%) were under the age of 18 years, and 81 (69.2%) were male patients. A maculopapular rash was noted in all patients, an inoculation eschar in 75 (64.1%), and regional lymphadenopathy occurred in 24 (20.5%). Five patients (4.3%) required ICU admission; no deaths occurred. Compared to paediatric patients, adults had significantly higher C-reactive protein (CRP) concentrations [88.80 mg/L (IQR 54.70–121.93) vs 60.00 mg/L (IQR 40.65–81.25); P = 0.009] and significantly lower platelet counts (146.83 ± 50.57 vs 187.43 ± 50.73 ×10⁹/L; P < 0.001). Given the small number of severe cases, multivariable modelling was not performed. More cases clustered in summer (57.3%) and autumn (40.2%). Despite most cases presenting in children and males, MSF appears to follow a relatively benign clinical course in this single-centre Libyan cohort. The inflammatory and haematological disturbance was more prominent in adult than paediatric patients. The small number of severe cases made prognostic modelling impossible. Further prospective multicentre serological and molecular confirmation studies are needed to help define disease burden and prognostic factors in Libya.